ANALISIS PENGARUH KOMPENSASI, PENDIDIKAN DAN PELATIHAN, SERTA MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS KOPERASI, PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN SOPPENG - Cahyo Sasmito (Universitas Tribhuwana Tunggadewi, 2013)
Evaluation Working performance of The Cooperation, Industry and Trade Board of Soppeng Regency has not reached to what expected by Soppeng’s community. This seemed to due to several factors such as compensation, edication and training, and motivation the employees. this study was aimed to describe the effects of compensation, education & training, and motivation on employee’s working performance of The Cooperation, Industry and Trade Board of Soppeng Regency. This study was conducted at the The Cooperation, Industry and Trade Board of Soppeng Regency from August 2012 to December 2012. All 38 employees of the board were used as respondents. Primary data were directly collected from respondents sing questionaires to obtained information related to compensation, education and training and motivation (as dependent variables), and employee’s working performance (as in independent variable). Data analyses covered validity and realibility of instruments and a linier regression. Results of this study showed that compensation, education and training and motivation simulatenously affected employee’s working performance of The Cooperation, Industry and Trade Board of Soppeng Regency. These three independent variables contrubuted 73,7% variation of the dependent variable (working performance). Partially, compensation and education and tranining significantly affected working performance whereas motivation did not significantly affect working performance. Education and training seemed to be the dominant factor affecting working performance of employees of The Cooperation, Industry and Trade Board of Soppeng Regency.